L’impact des mots du vocabulaire maritime sur l’environnement linguistique global du français acadien : l’exemple de haler - Gauvin, Karine (Canadian Journal of Applied Linguistics, 2006)
Studies on Acadian and Quebec French have clearly shown that these varieties are characterized by words of maritime origin that have evolved semantically. These words, along with other words, have been integrated in the language to form original lexical networks that differ from those of Standard French. The verb haler in Acadian French is such an example, as its presence has an impact on the global linguistic environment of Acadian French. The semantic extensions of certain words of maritime origin interact with words used in Standard French, which has an effect on their selection and their paradigmatic distribution. An examination of the various meanings of the verb haler (‘tirer’) will be followed by a study of its functional distribution in the language.